2010
DOI: 10.1093/cvr/cvq108
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of calmodulin from cardiac ryanodine receptor causes aberrant Ca2+ release in heart failure

Abstract: The defective inter-domain interaction between N-terminal and central domains within RyR2 reduces the binding affinity of CaM to RyR2, thereby causing the spontaneous Ca(2+) release events in failing hearts. Correction of the defective CaM binding may be a new strategy to protect against the aberrant Ca(2+) release in heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 25 publications
4
81
0
Order By: Relevance
“…Furthermore, dantrolene binds to the corresponding sequence (amino acids 601-620) of RyR2 (33,47) and has recently been proposed to have effects on cardiac RyR2 (24,50); however, no effect of the drug on the properties of native RyR2 channels has been observed in single channel analysis (12). Recent evidence has suggested that dantrolene may ameliorate abnormal RyR2-mediated Ca 2ϩ release associated with heart failure (HF) (24,31). In HF (7), it has been hypothesized that interdomain interactions between the NH 2 -terminal and central domains of the RyR2 channel become destabilized or unzipped [possibly through posttranslational modifications such as phosphorylation (1,30) or oxidation (44)], thus contributing to channel dysfunction and altering cellular Ca 2ϩ -handling properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, dantrolene binds to the corresponding sequence (amino acids 601-620) of RyR2 (33,47) and has recently been proposed to have effects on cardiac RyR2 (24,50); however, no effect of the drug on the properties of native RyR2 channels has been observed in single channel analysis (12). Recent evidence has suggested that dantrolene may ameliorate abnormal RyR2-mediated Ca 2ϩ release associated with heart failure (HF) (24,31). In HF (7), it has been hypothesized that interdomain interactions between the NH 2 -terminal and central domains of the RyR2 channel become destabilized or unzipped [possibly through posttranslational modifications such as phosphorylation (1,30) or oxidation (44)], thus contributing to channel dysfunction and altering cellular Ca 2ϩ -handling properties.…”
mentioning
confidence: 99%
“…The loss of Ca 2ϩ from the cell decreases SR Ca 2ϩ content and subsequently weakens myocyte contraction as less Ca 2ϩ is available for beat-to-beat activation of the contractile proteins (26,35). Recent investigations have suggested that dantrolene may correct the abnormal RyR2-mediated Ca 2ϩ release associated with HF by stabilizing the interdomain interactions of RyR2 and preventing diastolic SR Ca 2ϩ release (23,24,31).…”
mentioning
confidence: 99%
“…Recently, we found that domain unzipping seen in failing hearts also dissociates CaM as in the case of CPVT, and rebinding of CaM ameliorates the stability of the RyR2 [10,20]. These findings indicate that dissociation of CaM allosterically linked to domain unzipping plays a critical role in abnormal Ca 2+ handling as a common pathogenic mechanism underlying CPVT and heart failure, by which aberrant Ca 2+ release is induced.…”
Section: Discussionmentioning
confidence: 81%
“…In our previous study, we showed that CaM binding affinity of RyR is markedly decreased, thereby inducing spontaneous Ca 2+ leak which leads to contractile dysfunction and arrhythmia [9,10,20]. Moreover, in failing hearts we found that CaM-(Gly-Ser-His), which shows higher binding affinity to the RyR1 than CaM [21], stabilized the RyR2 channel, inhibited Ca 2+ leak, and improved myocyte function [10].…”
Section: Resultsmentioning
confidence: 95%
“…Whereas unzipping of N-terminal and central domains was associated with spontaneous SR Ca 2+ leak, dantrolene suppressed both unzipping and SR Ca 2+ leak (sparks) and ultimately delayed afterdepolarizations, which are common in heart failure. Additionally, dantrolene restores calmodulin (CaM) binding to RyR2, which is usually attenuated in heart failure [39] .…”
Section: Dantrolenementioning
confidence: 99%